2017
DOI: 10.1038/s41598-017-08971-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of SOX2 expression delineates an end-point for paclitaxel-effectiveness in breast cancer stem cells

Abstract: Tumor relapse in triple negative breast cancer patients has been implicated to chemoresistant cancer stem cells (CSCs), which under favorable conditions culminate in tumor re-formation and metastasis. Hence, eradication of CSCs during systemic chemotherapy is imperative. CSCs were sorted using immuno-phenotyping and aldefluor assay. Gene expression profiling of normal breast stem cells and breast CSCs from chemo-treated patients were carried out. Silencing SOX2 was achieved by siRNA method. Mammosphere culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 44 publications
5
93
0
1
Order By: Relevance
“…SOX2 is a master regulator that maintains stemness in embryonic stem cells (44) as well as self-renewal of CSCs in several malignancies (36,45). In addition, SOX2 also plays a critical role in drug resistance to paclitaxel (45) and gemcitabine (46) in several cancers. However, the function and epigenetic regulatory mechanism of SOX2 in BCSCs remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…SOX2 is a master regulator that maintains stemness in embryonic stem cells (44) as well as self-renewal of CSCs in several malignancies (36,45). In addition, SOX2 also plays a critical role in drug resistance to paclitaxel (45) and gemcitabine (46) in several cancers. However, the function and epigenetic regulatory mechanism of SOX2 in BCSCs remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated SOX2 expression is also associated with increased resistance to chemotherapy agents, although whether this is a direct effect is uncertain (Schrock et al, 2014). However, silencing SOX2 in breast cancer cells in culture leads to increased sensitivity to the chemotherapeutic agent paclitaxel and reduction in mammosphere formation (Mukherjee, Gupta, Chattopadhyay, & Chatterji, 2017), suggesting a direct effect of SOX2 expression on chemoresistance in cancer cells. In addition, elevated or ectopic SOX2 expression has also been associated with the progression of other cancers, including skin SCC (Boumahdi et al, 2014), glioblastoma (Annovazzi, Mellai, Caldera, Valente, & Schiffer, 2011), laryngeal squamous cell carcinoma (LSCC) (Yang, Hui, Wang, Yang, & Jiang, 2014), bladder cancer (Zhu et al, 2017), and small-cell lung cancer (Hussenet et al, 2010).…”
Section: Cancer Initiating Cells In Human Head and Neck Cancers (Hncs)mentioning
confidence: 99%
“…In addition, it was found that knockdown of SOX2 in pancreatic ductal adenocarcinoma cells increased the response to small-molecule inhibitors targeting MEK and AKT signaling (18). A recent study indicated that down regulation of SOX2 reduced invasiveness and increased sensitivity to paclitaxel by preserving the epithelial-like properties of breast cancer stem cells (19).…”
Section: Introductionmentioning
confidence: 99%